2021
DOI: 10.1101/2021.09.01.458647
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High diversity in Delta variant across countries revealed via genome-wide analysis of SARS-CoV-2 beyond the Spike protein

Abstract: The highly contagious Delta variant of SARS-CoV-2 has emerged as the new dominant global strain, and reports of reduced effectiveness of COVID-19 vaccines against the Delta variant are highly concerning. While there has been extensive focus on understanding the amino acid mutations in the Delta variant's Spike protein, the mutational landscape of the rest of the SARS-CoV-2 proteome (25 proteins) remains poorly understood. To this end, we performed a systematic analysis of mutations in all the SARS-CoV-2 protei… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…This is similar to previous studies indicating the I82T mutation as one of the most frequent mutations in the M protein in the USA, with a 116-fold increase from October 2020 to February 2021 [32]. Suratekar et al also reported I82T as one of the most prevalent mutations in the Delta variant in a systematic analysis of mutations from nearly 2 million SARS-CoV-2 genomes from 176 countries [33]. However, till 2020, D3G was reported as the most common mutation in this protein [22].…”
Section: Mutational Insights Among the Structural Proteins Of Sars-co...supporting
confidence: 89%
“…This is similar to previous studies indicating the I82T mutation as one of the most frequent mutations in the M protein in the USA, with a 116-fold increase from October 2020 to February 2021 [32]. Suratekar et al also reported I82T as one of the most prevalent mutations in the Delta variant in a systematic analysis of mutations from nearly 2 million SARS-CoV-2 genomes from 176 countries [33]. However, till 2020, D3G was reported as the most common mutation in this protein [22].…”
Section: Mutational Insights Among the Structural Proteins Of Sars-co...supporting
confidence: 89%
“…A high variation rate in genomes belonging to Delta has been described before (Suratekar et al . 2021 ), but in which direction is the VoC evolving? Although theoretically possible, is it likely that a given VoC will independently evolve to collect mutations similar to those that resulted in increased fitness in previous VoC, thus creating an ever more ‘successful’ VoC?…”
Section: What Do These Observations Mean For the Evolution Of Sars-co...mentioning
confidence: 99%
“…The Delta variant has multiple mutations distributed throughout its genome of which at least five are located within the S gene that encodes the spike protein [Suratekar et al, 2021]. Some of these individual mutations are shared by other variants but we noted that the combination of spike mutations L452R and T478K (corresponding to nucleotide positions T22917G and C22995A, respectively) within the receptor binding domain can effectively differentiate Delta from other variants.…”
Section: Primer and Probe Designmentioning
confidence: 81%